Relative importance of β(cyto)- and γ(cyto)-actin in primary mouse embryonic fibroblasts - Patrinostro, Xiaobai (Mol Biol Cell, 2017)
The highly homologous β (β(cyto)) and γ (γ(cyto)) cytoplasmic actins are hypothesized to carry out both redundant and unique essential functions, but studies using targeted gene knockout and siRNA-mediated transcript knockdown to examine β(cyto)- and γ(cyto)-isoform–specific functions in various cell types have yielded conflicting data. Here we quantitatively characterized actin transcript and protein levels, as well as cellular phenotypes, in both gene- and transcript-targeted primary mouse embryonic fibroblasts. We found that the smooth muscle α(sm)-actin isoform was the dominantly expressed actin isoform in WT primary fibroblasts and was also the most dramatically up-regulated in primary β(cyto)- or β/γ(cyto)-actin double-knockout fibroblasts. Gene targeting of β(cyto)-actin, but not γ(cyto)-actin, led to greatly decreased cell proliferation, decreased levels of cellular ATP, and increased serum response factor signaling in primary fibroblasts, whereas immortalization induced by SV40 large T antigen supported fibroblast proliferation in the absence of β(cyto)-actin. Consistent with in vivo gene-targeting studies in mice, both gene- and transcript-targeting approaches demonstrate that the loss of β(cyto)-actin protein is more disruptive to primary fibroblast function than is the loss of γ(cyto)-actin.